Microbial Methylation of Iodide in Unconfined Aquifer Sediments at the Hanford Site, USA - Bagwell, Christopher E.; Zhong, Lirong; Wells, Jacqueline R.; Mitroshkov, Alexandre V.; Qafoku, Nikolla P. (Frontiers in Microbiology, 2019)
Incomplete knowledge of environmental transformation reactions limits our ability to accurately inventory and predictably model the fate of radioiodine. The most prevalent chemical species of iodine include iodate (IO3-), iodide (I-), and organo-iodine. The emission of gaseous species could be significant loss or flux term but these processes have not previously been investigated at radioiodine impacted sites. We examined iodide methylation and volatilization for Hanford Site sediments from 3 different locations under native and organic substrate amended conditions at 3 iodide concentrations. Aqueous and gaseous sampling revealed methyl-iodide to be the only iodinated compound produced under biotic conditions. No abiotic transformations of iodide were measured. Methyl-iodide was produced by 52 out of 54 microcosms, regardless of prior exposure to iodine contamination or the experimental concentration. Interestingly, iodide volatilization activity was consistently higher under native (oligotrophic) Hanford sediment conditions. Carbon and nutrients were not only unnecessary for microbial activation, but supplementation resulted in > 3 fold reduction in methyl-iodide formation. This investigation not only demonstrates the potential for iodine volatilization in deep, oligotrophic subsurface sediments at a nuclear waste site, but also emphasizes an important role for biotic methylation pathways to the long-term management and monitoring of radioiodine in the environment.